Dampak Lingkungan Keluarga Terhadap Hasil Belajar Sosiologi Siswa SMAN 2 Tebas - Riama Al Hidayah; Mashudi Mashudi (Cetta: Jurnal Ilmu Pendidikan, 2021)
In their lifes, children will always be influenced by three aspects, namely family, children will always get the impact of three aspects, there are family, community, and school. The family environment is included in the first and foremost educational environment for children or students. In a family environment, parents should be able to set a good example for their children, so that this example will indirectly affect their children's learning outcomes at school. The objectives of this study include 1) To find out the description of the family environment of XI IPS students at 2 SHS Tebas West Kalimantan, 2) To determine the learning outcomes of students in XI IPS 2 SHS Tebas West Kalimantan, 3) To determine the impact of the family environment on XI IPS students at 2 SHS Tebas West Kalimantan learning outcomes. This study uses quantitative methods with a sample of 75 students. In this study, there are two hypotheses, including: 1) the null hypothesis (Ho), namely there is no impact between the family environment on student learning outcomes at SMAN 2 Tebas, and 2) the alternative hypothesis (Ha), namely there is an impact between the family environment on student learning outcomes at SMAN 2 Tebas. Based on the data analysis, the family environment variable with partial learning outcomes has a correlation coefficient of 0.101. This shows that there is an insignificant impact between the parents' family environment on learning outcomes. Based on the results of data analysis, researchers can conclude 1) The student's family environment is in the lower middle class family environment. 2) The majority of student learning outcomes have a moderate value. 3) The family environment obtained a partial correlation coefficient value of 17.9% with a low level of interpretation relationship, but had a positive impact on student learning outcomes.